4D MRI for the Localization of Parathyroid Adenoma: A Novel Method in Evolution. (March 2016) - Merchavy, Shlomo; Luckman, Judith; Guindy, Michal; Segev, Yoram; Khafif, Avi
The sestamibi scan (MIBI) and ultrasound (US) are used for preoperative localization of parathyroid adenoma (PTA), with sensitivity as high as 90%. We developed 4-dimensional magnetic resonance imaging (4D MRI) as a novel tool for identifying PTAs. Eleven patients with PTA were enrolled. 4D MRI from the mandible to the aortic arch was used. Optimization of the timing of image acquisition was obtained by changing dynamic and static sequences. PTAs were identified in all except 1 patient. In 9 patients, there was a complete match between the 4D MRI and the US and MIBI, as well as with the operative finding. In 1 patient, the adenoma was correctly localized by 4D MRI, in contrast to the US and MIBI scan. The sensitivity of the 4D MRI was 90% and after optimization, 100%. Specificity was 100%. We concluded that 4D MRI is a reliable technique for identification of PTAs, although more studies are needed.